Structural exchange pays off: Reciprocity in boards and executive compensations in US firms (1990-2015) - Olivier Godechot; Joanne Horton; Yuval Millo (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2019)
– We study the influence of the corporate board network on executive pay for 3,395 US firms over the period from 1990 to 2015. Drawing on structural anthropology and social exchange theory, we identify three elementary structures through which the interlocking network captures an obvious form of objective reciprocity between executives from different firms: restricted exchange, when two executives sit on each other's respective boards; delayed exchange, when y sits on the board of x after the end of x's mandate on the board of y ; and generalized exchange, when x sits on the board of y, who sits on the board of z, who sits on the board of x. Our results suggest that these ties, although not very common, are more frequent than those calculated by chance. We also find that the three structures of reciprocity have a positive impact on executive pay, especially on bonuses and total cash. We use the Sarbanes-Oxley Act (2002) as a natural experiment to confirm our first findings. The impact on pay disappears after 2004, once these types of exchanges are constrained. Although linked to executive pay, these structures are not tied to any indicator of firm performance. This leads us to interpret them as a rent extraction phenomenon.
Keywords: 330; executive pay; interlocks; social exchange; reciprocity; generalized exchange